Answer:
c. Put them alined straight and centered X to B to W and now you get the answer so it's C.
Answer:
-2x + 6
Step-by-step explanation:
Step 1: Define
f(x) = 3x + 2
g(x) = 4 - 5x
Step 2: Find f(x) + g(x)
3x + 2 + 4 - 5x
-2x + 6
The first two are correct because you have to understand and the questions are right good job w8th it
Answer:
Step-by-step explanation:
wwwwwwwwwwwwwwwwwwwwwwa
Answer:
Step-by-step explanation:
Recursive formula
tn = t_n-1 / 4
t2 = t1 / 4
t2 = 10240
t1 = 10240 / 4 = 2560
Explicit formula
tn = 10240 / 4^(n-1)
t4 = 10240 / 4^(4 - 1)
t4 = 10240 / 4^3
t4 = 10240 / 64
t4 = 160
t8 = 10240 / 4^7
t8 = 0,625